Effect of Loan To Deposit Ratio (LDR), Inflation, Intellectual Capital and Net Profit Margin (NPM) to Profitability in Conventional Banks Listed in Indonesia Stock Exchange during 2014-2018 - Wenni Anggita; Chandra Prasadhita (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to analyze the effect of Loan to Deposit Ratio, Inflation, Intellectual Capital and Net Profit Margin on profitability. This research uses this type of research with a quantitative approach by using panel data and processed using e-Views software. The sample used was 29 Conventional Banks listed on the Indonesia Stock Exchange 2014-2018. The results of this study reveal that the Loan to Deposit Ratio, Inflation and Net Profit Margin have a positive effect on profitability. Intellectual Capital does not have a positive effect on profitability.